Strategy for Elderly Women as Street Vendor in Kisaran Timur District - Rosramadhana, Rosramadhana; Hutajulu, Afriyeni; Sudirman, Sudirman; Pujiraharjo, Sidarta (Universitas Andalas, 2024)
This research reveals the strategies of elderly female street vendors in Kisaran Timur District. The aim of this research is to determine the background, strategies and perceptions of society towards elderly women. The method used in this research is a descriptive qualitative approach. The informants in this study were six female street vendors who were determined using purposive sampling. Data collection techniques were carried out through observation, interviews, literature study and documentation. The data analysis technique goes through the stages of data reduction, data presentation, and then drawing conclusions. The results obtained from this research indicate that the background of an elderly female street vendor who works to fulfill the daily economy. The strategy used is to build relationships with consumers. The relationship contained in the strategy of elderly women with family elements who become regular customers, builds communication with consumers with the aim of building brotherhood. Public perception of elderly female street vendors, the emergence of feelings of sympathy, as well as positive perceptions of elderly women who work as street vendors. The conclusion from these findings is that elderly women work to survive, a form of struggle for the family, a habit of working hard.